2022
DOI: 10.3390/w14060836
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of R&D Input on Operating Income of Chinese Wastewater Treatment Companies—With Patent Performance as a Mediating Variable

Abstract: The Chinese government is actively promoting green and low-carbon transformation for economic and social development, especially in the wastewater treatment industry. This article uses regression analysis to study the impact of company R&D input on patent performance and company operating income for different regulatory environments and regions. Companies in the wastewater treatment industries of the Shanghai and Shenzhen stock exchanges from 2013 to 2020 are selected as research samples. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Yun & Kim (2021) have come to the same conclusion regarding the effect of R&D investment on operating profit. Xu et al (2022) reached a similar conclusion when the influence of patent activity, as a moderator of the influence of R&D activities, on operating profit is in question. Lee et al (2015) found that internal R&D-generated and purchased patents have beneficial effects on profit.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Yun & Kim (2021) have come to the same conclusion regarding the effect of R&D investment on operating profit. Xu et al (2022) reached a similar conclusion when the influence of patent activity, as a moderator of the influence of R&D activities, on operating profit is in question. Lee et al (2015) found that internal R&D-generated and purchased patents have beneficial effects on profit.…”
Section: Discussionmentioning
confidence: 68%
“…The wastewater treatment companies were chosen for the research sample and the examined period is from 2013 to 2020. The findings indicate that the positive impact of R&D on operating income is moderated by patent activities (Xu et al, 2022).…”
Section: The Relation Between Randd Activity and Business Performance...mentioning
confidence: 89%
See 1 more Smart Citation
“…Caglar and Nisel (2017) state that marketing and R&D expenses in the manufacturing industry hurt Earnings before interest and tax (EBIT) and net earnings. Xu et al (2022) explored the effect of R&D input on the operating earnings of the wastewater companies listed on the Shanghai and Shenzen stock exchanges for the period from 2013 to 2020. The findings showed that R&D input has a positive and significant effect on company operating income.…”
Section: The Link Between Randd Investments Rdi and Earningsmentioning
confidence: 99%
“…Firstly, through examining the industrial policies of developed countries and regions such as the United States, Germany, and the European Union, it is clear that technological innovation is fundamental to renewable energy industrialization and that governments globally have spared no effort in supporting the research and development of renewable energy technologies [3,4]. In terms of renewable energy industry policies, all countries are basically the same, with policy being divided into three main areas: strengthening the protection of intellectual property rights, improving the investment environment, and establishing a renewable energy market, all of which are behind the booming development of the industry [5][6][7]. Secondly, in terms of research into government subsidies and innovative performance, most scholars believe that governments implement government subsidies to guide the flow of industrial resources and promote their optimal allocation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%